Modélisation des ondes infragravitaires : de l'échelle régionale à l'échelle mondiale - Rawat, Arshad (Université de Bretagne occidentale, 2015)
Wind-generated surface gravity waves are ubiquitous at the ocean surface. Their period varies between 2 and 25 seconds, with wavelength varying between a few meters to several hundreds of meters. Longer and, lower frequency surface gravity waves, called infragravity (IG) waves, are associated to these short, high frequency wind-generated waves. These infragravity waves have dominant periods comprised between 30 seconds and 10 minutes, and, when they propagate freely, with horizontal wavelengths of up to tens of kilometres, as given by the linear surface gravity wave dispersion relation. Outside of surf zones, the vertical amplitude of these infragravity waves is of the order of 1-10 cm, while the amplitude of wind-generated waves is of the order of 1-10 m.Given the length scales of the infragravity wavelengths, and despite the fact that the infragravity wave field exhibits much smaller vertical amplitudes than the high frequency wind-driven waves, the infragravity wave field will be a significant fraction the signal measured by the future Surface Water Ocean Topography satellite (SWOT) mission. This infragravity wave field will have to be characterized in order to achieve the expected precision on dynamic height measurements. It appears likely that the above mentioned precision will not be feasible for high sea states and long and steep swells. One of the aims of this thesis was to provide a first quantification of these associated uncertainties. Beyond the SWOT mission, the quantification of the IG wave field is a key problem for the understanding of several geophysical phenomena, such as the understanding of microseisms and ice shelves break up. Les vagues de surface générées par le vent, généralement appelées houle ou mer de vent, sont omniprésents à la surface de I'océan. Ils sont et ont des périodes variant entre 2 et 25 secondes et de longueur d'onde variant de quelques mètres à plusieurs centaines de mètres. Il existe aussi des ondes plus longues et, à plus basse fréquence appelés ondes infragravitaires ...